2014
DOI: 10.1001/jamaneurol.2013.6001
|View full text |Cite
|
Sign up to set email alerts
|

Population Screening for Variant Creutzfeldt-Jakob Disease Using a Novel Blood Test

Abstract: IMPORTANCE Our study indicates a prototype blood-based variant Creutzfeldt-Jakob disease (vCJD) assay has sufficient sensitivity and specificity to justify a large study comparing vCJD prevalence in the United Kingdom with a bovine spongiform encephalopathy–unexposed population. In a clinical diagnostic capacity, the assay’s likelihood ratios dramatically change an individual’s pretest disease odds to posttest probabilities and can confirm vCJD infection. OBJECTIVES To determine the diagnostic accuracy of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 46 publications
0
32
0
1
Order By: Relevance
“…This assay was shown to be more efficient than IP with antibodies, and allowed the detection of PrP TSE in human whole blood spiked with high dilutions (up to 10 210 ) of vCJD-infected brain homogenate, and in the whole blood of 15 of 21 symptomatic patients with vCJD H. Abdel-Haq with 71.4 % sensitivity and 100 % specificity. This assay was recently validated by the same research group, using a larger number of samples, including healthy and potentially crossreactive patient populations (Jackson et al, 2014). This validation study not only confirmed the previously determined specificity and sensitivity of the assay for vCJD infection in blood, but also identified 2 of 105 patients who were positive for sCJD, indicating that this assay was also sensitive for significantly lower levels of prion infectivity, such as those associated with sCJD (Jackson et al, 2014).…”
Section: Solid-state Binding Matrixmentioning
confidence: 57%
See 2 more Smart Citations
“…This assay was shown to be more efficient than IP with antibodies, and allowed the detection of PrP TSE in human whole blood spiked with high dilutions (up to 10 210 ) of vCJD-infected brain homogenate, and in the whole blood of 15 of 21 symptomatic patients with vCJD H. Abdel-Haq with 71.4 % sensitivity and 100 % specificity. This assay was recently validated by the same research group, using a larger number of samples, including healthy and potentially crossreactive patient populations (Jackson et al, 2014). This validation study not only confirmed the previously determined specificity and sensitivity of the assay for vCJD infection in blood, but also identified 2 of 105 patients who were positive for sCJD, indicating that this assay was also sensitive for significantly lower levels of prion infectivity, such as those associated with sCJD (Jackson et al, 2014).…”
Section: Solid-state Binding Matrixmentioning
confidence: 57%
“…This assay was recently validated by the same research group, using a larger number of samples, including healthy and potentially crossreactive patient populations (Jackson et al, 2014). This validation study not only confirmed the previously determined specificity and sensitivity of the assay for vCJD infection in blood, but also identified 2 of 105 patients who were positive for sCJD, indicating that this assay was also sensitive for significantly lower levels of prion infectivity, such as those associated with sCJD (Jackson et al, 2014). However, this assay is still limited by its insufficient sensitivity for the detection of asymptomatic individuals with vCJD who are subclinical carriers, or at the preclinical stage of the disease.…”
Section: Solid-state Binding Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, infectivity was reported in the plasma of two out of four patients affected by sporadic CJD (sCJD) (11). Although similar levels of PrP TSE have been detected in spleens, tonsils, and lymph nodes of vCJD and sCJD patients by Western blotting (12), the identification of this protein in the blood of individuals afflicted with the latter by various methods, including PrP TSE capture coupled to direct immunodetection of surface-bound material (6), capillary electrophoresis (13), and protein misfolding cyclic amplification (PMCA) coupled to surrounding optical fiber immunoassay (12), has been highly elusive for decades, with only two cases recently reported (8). Nevertheless, extensive epidemiological data continue to provide no evidence of human-to-human transmission of sCJD through blood transfusion (14).…”
mentioning
confidence: 99%
“…However, the occurrence of vCJD cases caused by administration of prion-infected human blood has highlighted the realistic opportunity for the development of a blood-based diagnostic test for this condition. Recent developments have shown promise with the detection of vCJD-positive blood samples from clinical vCJD cases by immuno-biochemical selection of disease-associated PrP, without the use of PK [42,43], and by detection of PK-resistant PrPSc following PMCA [44]. Since transmissibility is a defining hallmark of prion diseases, it will be important to develop a reasonably rapid and versatile confirmatory prion infectivity bioassay to supplement these biochemical-based prion diagnostic assays.…”
Section: Discussionmentioning
confidence: 99%